INFLUENCE OF THE DIFFERENTIAL STRESS AND THE ORGANIC PATCHES ON THE CRACK PROPAGATION IN SHALES BY A DEMFV SIMULATION - Teixeira, Marcello Goulart; Donzé, Frederic-Victor; Papachristos, Efthymios; Renard, François; Panahi, Hamed; Scholtés, Luc (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The coupling between chemical reactions and deformation in rocks can induce permanent damage and cracking that facilitate the circulation of fluids at large scale. This coupling process has been observed in various geological systems as weathering and erosion of rocks on the surface, hydration of the lower crust, sediment dehydration in subduction zones, serpentinization of oceanic crust or sediment rock. Among the sedimentary rocks, shale has gained prominence due to growing unconventional exploitation of gas and oil. In this geological material, the coupling between organic matter maturation and the creation of micro-crack connectivity is one of the mechanisms proposed to explain the primary migration of hydrocarbons. The aim of this work is to study the influence of the differential stress and the density of organic patches on the crack propagation in shales. To this end, the hydromechanical version of the open source Discrete Element Method (DEM) code YADE is used to simulate the organic material dilatancy-induced cracking. It is presented some numerical simulations of crack propagation and an analysis of the influence studied.